Current Agriculture Practices: Baseline Survey Report: Central Highlands Ecoregion Foodscape (CHEF) - Gizaw, Desta; Desalegn, Henok; Michael, Kinyua; Nyawade, Shadrack; Assefa, Banchayehu; Boaz, Waswa (International Crops Research Institute for the Semi-Arid Tropics, 2025)
The Nature Conservancy (TNC) Central Highlands Ecoregion Foodscapes (CHEF) Use Case targets eleven counties in the central highland region of Kenya that transition from water towers, smallholder transition zone, semiarid production zone, to rangelands. The mission of the Use Case is to improve and sustain the health, diversity, and productivity of the croplands and rangelands to meet the needs of the present and future communities. The interaction of land use systems and agrifood systems in the region is the driver of production decline and depletion of ecosystem services and biodiversity. The CHEF Use Case embeds a foodscapes-scale approach along the transitions to design, validate, and action that are sensitized to local contexts. The approach fosters bridging traditional knowledge and scalable nature-based interventions to drive and achieve an inclusive and sustainable food systems transformation and to accelerate system-wide change. The Use Case aims to catalyze the implementation of regenerative practices and innovations across the transition zones, representing the diversity of geographic and food production archetypes.